Impact of the COVID-19 pandemic on the experience and mental health of university students studying in Canada and the UK: a cross-sectional study. Issue 1 (24th January 2022) - Appleby, Jennifer A; King, Nathan; Saunders, Kate E; Bast, Anne; Rivera, Daniel; Byun, Jin; Cunningham, Simone; Khera, Charandeep; Duffy, Anne C
Abstract : Objectives: To explore the impact of the COVID-19 pandemic on the experiences and mental health of university students. Design: A cross-sectional study consisting of an electronic survey about students' experiences and concerns during the pandemic and the associated impact. In addition to the quantitative analysis, free-text responses were extracted and analysed using a framework technique. Setting: Queen's University in Canada and the University of Oxford in the UK. Participants: Undergraduate students at Queen's University and first-year undergraduate students at the University of Oxford were invited to complete the COVID-19 supplement survey. This study included data from 3013 Queen's students as the primary focus and 339 Oxford students as a secondary comparison. Results: Females at Queen's reported greater adherence to government recommendations to prevent the spread of COVID-19 (91.3% vs 86.7%, χ 2 p<0.01) and were more likely to self-isolate (63.9% vs 57.0%, χ 2 p<0.01) than males. A similar trend was seen among Oxford students. Students' concerns were wide ranging including those related to their learning experience, finances and future academic and career prospects. 78.9% of Queen's students and 50.4% of first-year Oxford students reported worries about the long-term impact on their academic and job prospects. A sizeable proportion of students also reported that the pandemic negatively impacted their plans to continue at university (29.4% of Queen's, 14.2% of Oxford) and disrupted activities important to their mental well-being. Key themes identified in the qualitative component included the negative impacts of social isolation, challenging academic changes and disruption to support services and means of coping. Conclusions: Overall, findings underscore the importance of addressing areas of student concern and the aspects of student life negatively impacted by the pandemic in order to maintain student well-being and support a successful university experience.